Estudio dendroclimático de Juglans neotropica Diels en cuatro ecosistemas andinos de la provincia de Loja al sur de Ecuador, previo a la obtención del título de Ingeniero Forestal - Reyes Andrade, Diego Israel (2024)
The Andean region is known for its rich biodiversity and high level of endemism, yet it faces serious threats due to land use changes. Juglans neotropica Diels, a native tree of the Andes growing at altitudes of 1,800 to 3,000 meters above sea level, is renowned for its diverse uses and ecosystem services it provides to the local people of the Loja province, Ecuador. Therefore, this research analyzes the relationship between its growth and precipitation in four different forest ecosystems. Dendrochronological techniques were used to examine the annual diameter growth of Juglans neotropica in the ecosystems of Parque Universitario Francisco Vivar Castro (PUFVC), Shucos, El Tundo, and Saraguro. Wood samples were collected to analyze growth rings. Using RStudio software and climate data from the Instituto Nacional de Meteorología e Hidrología del Ecuador- INAMHI (1990-2013), and growth rates were correlated with local precipitation. Results varied significantly among the sites, with average annual growth rates of 6.02 mm in El Tundo, 6.52 mm in Shucos, 6.50 mm in PUFVC, and 8.28 mm in Saraguro. The correlation between growth and precipitation was positive only in El Tundo (r = 0.39), while negative correlations were observed in the other sites (Shucos: r = -0.29, Saraguro: r = -0.16, PUFVC: r = -0.43), suggesting that other environmental factors are influencing their growth. This study highlights the importance of having precise climatic data to better understand the dynamics of forest growth in response to climate variations.